OPTIMALISASI PENINGKATAN PENJUALAN SAYUR HIDROPONIK MELALUI PELATIHAN STRATEGI PEMASARAN DIGITAL DENGAN MEDIA SOSIAL TIKTOK - Aida Vitria; Abdurrahim; Ana Sofia Herawati; Purboyo; Amalia Wahyuni; Siti Zainab (PT. Jurnal Center Indonesia Publisher, 2025)
The digital marketing strategy training activity using the TikTok social media platform for hydroponic farmers in Pandahan Village aims to enhance their capability in digitally marketing hydroponic vegetable products. This training was designed to provide both theoretical understanding and practical hands-on experience in creating creative content, utilizing TikTok Shop, and TikTok Ads as promotional tools. The training results demonstrated a significant increase in participants' knowledge and skills in leveraging TikTok features for digital marketing. The implementation carried out by the participants successfully expanded their market reach and increased consumer interaction through their TikTok accounts. Despite challenges related to the need for ongoing mentoring, this activity has had a tangible positive impact on the development of local hydroponic businesses. This training is expected to become a starting point for business actors to continue innovating and optimizing digital marketing strategies to face the dynamics of the modern market.